The leader's guide to negotiation : how to use soft skills to get hard results - Horton, Simon (New York : Pearson Education, 2016)
PLAY ON YOUR TERMS Negotiation is THE core business skill. It is fundamental to everything we do that involves other people, whether that's asking for a raise, pitching an idea or deciding who gets the coffee. The Leader's Guide to Negotiation is a highly practical guide to getting the most out of your business interactions, whilst building stronger relationships to boot. From achieving win-win outcomes to problem-solving and building trust, it equips you with failsafe strategies for conducting successful and positive negotiations. 'An entertaining, immediately useful book that goes beyond a.